Strengthening Campus Disaster Readiness Through Standardized Operational Protocols and Unified University Command Systems - Ra’ad Hamudi (JURNAL ILMIAH GEMA PERENCANA, 2026)
This policy article comprehensively examines the urgency of transforming crisis management governance within higher education institutions, which has historically remained fragmented. This abstract outline a profound analysis of the phenomena of sectoral ego and leadership dualism, which serve as primary obstacles to the effectiveness of emergency response on campus. The core issue addressed is the lack of consistency in operational procedures across units and the weakness of command unity, resulting in decision-making paralysis during critical situations. To formulate applicable solutions, this article applies a descriptive-qualitative policy analysis methodology utilizing William N. Dunn’s evaluation criteria, encompassing effectiveness, efficiency, adequacy, responsiveness, and technical feasibility. Through the scoring of various policy alternatives, it was determined that establishing regulations to synchronize cross-unit operational protocols is the most crucial step for immediate implementation. The analysis results recommend the issuance of a Rector's Decree regarding Cross-Unit Standard Operating Protocols and a Rector's Regulation concerning the Institutional Emergency Command System as a juridical foundation to unify all university resources under a single linear operational control. The implementation of this policy is projected to reduce fatality risks and ensure the continuity of academic functions post-disaster by transforming organizational culture from exclusive unit asset ownership toward inclusive collective resource collaboration. Thus, strengthening this policy is not merely an administrative effort but a long-term defensive strategy to create an educational environment with high resilience against both natural and non-natural disaster threats in the future.